2023
DOI: 10.1186/s12879-023-08018-0
|View full text |Cite
|
Sign up to set email alerts
|

The factors associated with the trend in incidence of Bacteraemia and associated mortality over 30 years

Abstract: Background Studies have reported increased incidence of BSI over the past decades and indicate that it is necessary to investigate the causes. The aim of this study was to determine the factors affecting trends in the incidence of bacteraemias and associated mortality. Methods We conducted a retrospective cohort study assessing prospectively collected data of all clinically significant bacteraemias between 1991 and 2020 in a 450-bed hospital. We de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Age and septic shock have been identified as independent risk factors for bloodstream infections for more than 30 years [43]. In this study, the results showed that patients supplemented with vitamin D were significantly older than those not given vitamin D. Regarding potential reasons, as previously reported, elderly people are more likely to face the risk of vitamin D deficiency and osteoporosis [44,45].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Age and septic shock have been identified as independent risk factors for bloodstream infections for more than 30 years [43]. In this study, the results showed that patients supplemented with vitamin D were significantly older than those not given vitamin D. Regarding potential reasons, as previously reported, elderly people are more likely to face the risk of vitamin D deficiency and osteoporosis [44,45].…”
Section: Discussionsupporting
confidence: 57%
“…As displayed in Table 5, the primary outcomes showed that the vitamin D supplementation group had lower in-hospital mortality (21.5% vs. 29.7%), as well as 28-day (19.5% vs. 26.7%) and 90-day (23.8% vs. 32.3%) mortality rates. As for the disease severity-related scores, SOFA (6 (4-8) vs. 7 (4-10)) and APS III (54 (43-73) vs. 62 (48-82)) scores were significantly lower in the patients with sepsis supplemented with vitamin D compared to those who did not receive vitamin D. Although the SAPS II score (40 (32-49) vs. 42 (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)) was lower in the vitamin D supplementation group, no statistical differences were found between the two cohorts (p = 0.115). Consistently, there were no significant differences for the LOS in the ICU and hospital between the two groups (p = 0.988 and p = 0.207, respectively).…”
Section: Baseline Characteristics Clinical Outcomes Post Psmmentioning
confidence: 97%
“…This is consistent with a previous finding showing that Escherichia coli, Staphylococcus aureus, Klebsiella pneumoniae and Streptococcus pneumoniae were the most commonly isolated organisms in community-acquired BSIs[ 8 ]. In recent years, it has been reported that respiratory tract, urinary tract, and intra-abdominal infections are the main sources of sepsis and sepsis shock[ 9 , 10 ], and gram-negative bacteraemia has a higher frequency in the ICU[ 11 ]. Similarly, our study also showed that respiratory tract infection was the main reason for admission to the ICU but the patients had a lower rate of BSIs.…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus epidermidis is a gram-positive bacterium found in the skin and nasal cavity. Although it is generally not harmful, it can pose a risk for patients who are in a compromised condition such as those taking immunosuppressive drugs and have prostheses such as catheters and medical devices in the body [ 1 , 7 ]. In addition, a patient whose heart valve is regurgitant and stenotic or who has congenital heart defects is considered at high risk for infective endocarditis [ 1 ].…”
Section: Discussionmentioning
confidence: 99%